ETHICAL ISSUES SURROUNDING THE USE OF INFORMATION IN HEALTH CARE - Jayasundra, Chaminda Chiran (Malaysian Journal of Library and Information Science, 2004)
As a result of rapid technological and economic expansion throughout the world, society is confronted with new requirements. For the success of the medical practice, even with the rapid changes in technology and the medical field, practitioners involved in the use of patients’ information are obliged to continue to behave ethically. This paper reviews the ethical challenges raised in the use of patients’ information for medical and other purposes. It also discusses the values underlining the ethical issues and their importance in the use of patients’ information in the doctor and patient context. The issues surrounding the use of patients’ information such as secrecy and confidentiality are raised and potential problems in the area, policy issues which must be addressed by those concerned with the confidentiality and secrecy of health information and the germane legal issues are also discussed. Moreover, this is a review of the current status of the health care information ethics with particular reference to the United Kingdom, United States, Canada, Australia and developing countries. Finally, it concludes that the emerging field of health care information ethics will require careful thought and insights from an international collection of ethicists.